2007
DOI: 10.1111/j.1365-2249.2007.03514.x
|View full text |Cite
|
Sign up to set email alerts
|

Substance P regulates macrophage inflammatory protein 3α/chemokine C-C ligand 20 (CCL20) with heme oxygenase-1 in human periodontal ligament cells

Abstract: SummaryAlthough substance P (SP), a potent proinflammatory peptide, is involved in inflammation and immune responses, the effect of SP on the expression of macrophage inflammatory protein 3a [MIP-3a, chemokine C-C ligand 20 (CCL20)] in periodontal ligament (PDL) cells is unknown. Equally enigmatic is the link between SP, the stress protein heme oxygenase-1 (HO-1), and CCL20 production. We investigated whether SP induces the release of chemokine CCL20 from immortalized PDL (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 44 publications
(68 reference statements)
1
22
0
Order By: Relevance
“…[19][20][21][22][23][24] In the present study, we found that MS increased HO-1 mRNA and protein expression in PDLCs. These findings are consistent with our previous study in which osteogenic differentiation Figure 4.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…[19][20][21][22][23][24] In the present study, we found that MS increased HO-1 mRNA and protein expression in PDLCs. These findings are consistent with our previous study in which osteogenic differentiation Figure 4.…”
Section: Discussionsupporting
confidence: 66%
“…21,22,24 Increases in the expression of HO-1, BMP-2, BMP-7, and Runx-2 resulting from treatment with LPS and MS were attenuated by preincubation with selective inhibitors of p38, ERK, PI3K, PKG, and NF-kB (SB203580, U0126, LY294002, KT5823, and PDTC, respectively). These results suggest that LPS-induced and MS-induced HO-1 and BMP expression occurs via the activation of p38, ERK MAPK, PI3K, PKG, and NF-kB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported that the HO-1 pathway is a key mechanism for both the adaptation of cells to stressful conditions and their recovery from injurious events in human pulp and PDL cells [27][28][29][30][31][32]. Moreover, HO-1 has therapeutic potential in hepatoprotection [33], inflammatory arthritis [34], psoriasiform skin lesions [35], neuroinflammation [36], inflammatory bowel disease [37], and periodontitis [15].…”
Section: Introductionmentioning
confidence: 95%
“…Previously, we reported that the HO-1 pathway plays a key role in the adaptation of cells to stressful conditions and the recovery of HDPCs and periodontal ligament cells (PDLCs) from injurious events (7)(8)(9)(10)(11)(12). Moreover, several studies have shown that HO-1 expression is related to adipogenesis in human mesenchymal stem cells (MSCs) (13), osteoblastic differentiation in PDLCs (7,12), and neuronal differentiation in MSCs (14).…”
mentioning
confidence: 97%